Do medically unexplained symptoms matter? A prospective cohort study of 300 new referrals to neurology outpatient clinics. Issue 2 (1st February 2000) - Carson, Alan J; Ringbauer, Brigitte; Stone, Jon; McKenzie, Lesley; Warlow, Charles; Sharpe, Michael
Abstract : OBJECTIVES: To determine ( a ) the proportion of patients referred to general neurology outpatient clinics whose symptoms are medically unexplained; ( b ) why they were referred; ( c ) health status and emotional disorder in this group compared with patients whose symptoms are explained by "organic" neurological disease. METHODS: The prospective cohort study with case note follow up at 6 months was carried out in the regional neurology service in Lothian, Scotland with 300 newly referred outpatients. Neurologists rated the degree to which patients' symptoms were explained by organic disease (organicity), GPs' reasons for referral, health status (SF-36), anxiety, and depressive disorders (PRIME-MD), RESULTS: Of 300 new patients 11% (95% confidence interval (95% CI) 7%-14%) had symptoms that were rated as "not at all explained" by organic disease, 19% (15% to 23%) "somewhat explained", 27% (22% to 32%) "largely explained", and 43% (37% to 49%) "completely explained" by organic disease. Reason for referral was not associated with "organicity". Comparison of these groups showed that although physical function was similar, the median number of physical symptoms and pain were greater in patients with lower organicity ratings (p<0.0005, p<0.0005). Depressive and anxiety disorders were more common in patients with symptoms of lower organicity (70% of patients in the not at all group had an anxiety or depressive disorder compared with 32% in the completely explained group (p<0.0005). CONCLUSION: One third of new referrals to general neurology clinics have symptoms that are poorly explained by identifiable organic disease. These patients were disabled and distressed. They deserve more attention.